Theoretical Foundations and Application of Photonic Crystals - Vakhrushev, Alexander (IntechOpen, 2018)
This book is devoted to the description of research and design of photonic crystals. Topics included in the book cover a wide range of research in the field of theoretical analysis and experimental investigation: the electromagnetic field in the photonic crystal, propagation of waves in the gyrotropic magnetophotonic crystals, low one-photon absorption, ultratransparent photonic crystals, colloidal assembly, photonic crystal application for development of all-optical computational system, design strategies for PC devices, self-organization of liquid crystalline nanostructures, and optical diodes. This book will be useful for engineers, technologists, researchers, and postgraduate students interested in the research, design, fabrication processes, and applications of photonic crystals.